The Whole-Genome Sequencing and Hybrid Assembly of Mytilus coruscus - Li, Ronghua; Zhang, Weijia; Lu, Junkai; Zhang, Zhouyi; Mu, Changkao; Song, Weiwei; Migaud, Herve; Wang, Chunlin; Bekaert, Michaël (Frontiers in Genetics, 2020)
The hard-shelled mussel (Mytilus coruscus) is an economically important shellfish, which has been cultivated for the last decade. Due to over-exploitation, most mussel stocks have dramatically declined. Efforts to study this species' natural distribution, genetics, breeding and cultivation have been hindered by the lack of a high-quality reference genome. To address this, we produced a hybrid high-quality reference genome of M. coruscus using a long-read platform to assemble the genome and short-reads, high-quality technology to accurately correct for sequence errors. The genome was assembled into 10,484 scaffolds, a total length of 1.90 Gb and a scaffold N50 of 898 kb. Ab initio annotation of the M. coruscus genome assembly identified a total of 42,684 genes. This accurate, reference genome of M. coruscus provides an essential resource with the advantage of enabling the genome-scale selective breeding of M. coruscus. More importantly it will also help the deciphering of the speciation and local adaptation of the Mytilus species.